Scandinavian Model in Russia: Potential for Use - DANKO, T. P.; CHAYKOVSKAYA, L. A.; KISELEV, V. M.; SMELOV, P. A.; NEDELKIN, A. A.; SEKERIN, V. D. (Journal of Advanced Research in Law and Economics, 2019)
This article analyzes the issues of marketing positioning of countries in the innovation sphere. Today, the level of development and dynamism of innovation create the basis for sustainable economic growth. The concept of ‘innovation’ is closely related to the concepts of ‘novelty’, ‘invention’, ‘discovery’, which are products of creativity.